Important Features of a Military Teacher in Teaching Military Sciences - Qodirov Otabek Mahammadjonovich; Azimov Ravshanbek Husanovich (Genius Journals, 2021)
The article discusses the problems of professional personal qualities. Also, the characteristics of the psychological personalities of different professionals. The article describes the educational impact of the officer on the personnel units and the important features of the military educator
Keywords: Teacher culture; tact; axiological; intelligence